Warm Colors, the Encouragement - Wahidiyat, Mita Purbasari (Bina Nusantara University, 2021)
The research discussed the warm colors, such as yellow, orange, and red, as individual colors with a composition that could have a different impact on color connoisseurs depending on the background and context. The color was one design element that was rarely noticed but often used in everyday life. Color adds not only the beauty of an object but also the ability to manipulate the eyes and mind, often used to communicate without words. Using the right color at the right time and place could quickly send a message that was both fun and sad. The same color could mean different things in different cultural, social, economic, and political settings. Different cultures endowed color with different meanings depending on many things. As for color users, it was good to understand the effects of colors that were likely to occur to minimize the negative things. The research method applied was a qualitative narrative by collecting data from the literature, interviewing users and connoisseurs of color, observing, and analyzed. It is found that warm colors are often interpreted as bad things for some people in Jakarta, but they can also become symbols of courage and passion. It is hoped that these research results can be used as a rationale for making design work.